UPAYA MENINGKATKAN HASIL BELAJAR IPA SISWA MELALUI METODE PEMBELAJARAN KOOPERATIF TIPE STAD SISWA KELAS VA SDN 021 TANJUNG PALAS KECAMATAN DUMAI TIMUR KOTA DUMAI - Sabarina Br. Bangun (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
Class action research aims to improve learning outcomes a fifth grade science students SDNegeri 021 Tanjung Palas Kecamatan Dumai Timur Kota Dumai STAD cooperative method.The subjects were students of class V A SD Negeri 021 Tanjung Palas Kecamatan DumaiTimur Kota Dumai totaling 26 students. The data used in this study is the result of studentlearning, student activities, complete learn student and teacher activities. The instrument usedin this study consisted of two research instruments are instruments learning device consists ofa syllabus, lesson plan (RPP), student worksheet (LKS) and data collection instrumentsconsisted of the observation sheet student activity, observation sheet activities of teachers, atest sheet. The results showed mastery learning before the cycle I and II is (69.7) has not beencompleted in cycle 1 (75.07) completed, based on the results of the test on the second cycle(80.9). It can be concluded from the results of study A fifth grade science students SD Negeri021 Tanjung Palas Kecamatan Dumai Timur Kota Dumai can be increased through STADcooperative method.